The succession of Imam Hassan (P) in the thought of Judge Abd al-Jabbar Mu'tazili (d. 415 AH) - Yusuf Saud Al-Sultan , Lect . Dr. Aqil (Basra studies journal, 2026)
This research deals with the succession of Imam Hassan (P) in its legal and political aspects in the thought of Judge Abd al-Jabbar Mu'tazili. This research sheds light on what Imam Hassan's succession represents in the thought of one of the most prominent figures of the Basra Mu'tazili school The research finds that Judge Abd al-Jabbar's view is divided between preferring Imam Hassan (P) over the people of his time and his rejection of the claim that he was the designated successor. The study also examines his defense of the legitimacy of treaty with Muawiya and its impact on the legitimacy of Imam Hassan's succession, and he accepted money from Muawiya. Overall, Judge Abd al-Jabbar's view of Imam Hassan's succession is complicated Between the negative and the positive in evaluating this caliphate.